A mini review on recent advancements in inclined solar still. (November 2022) - Saravanakumar, R.; Venugopal, Jayaprakash; Udagani, Chikkappa; Thiyagarajan, V.; Kumar, S.K. Nandha; Karnan, Lokanayaki; Kabeel, Abd Elnaby; Madhu, B.; Sathyamurthy, Ravishankar
Abstract: Water shortage is a global problem, and the demand for fresh water is growing at an ever-increasing rate. The only method to meet the demand for water is via water filtration. Water purification may be done in a variety of methods, including cleaning saltwater or holding rainfall and then releasing it into the environment. There are still several kinds of solar still are available, which may be utilized to improve the amount of water that is generated. The inclined solar still (ISS) is a particularly successful option because it has a large outer water surface to supplement the normal potable water production, as well as because it has a shallow depth of water to increase the overall efficacy of the inclined solar still. Increasing the water's surface area has been the subject of much investigation. As a result of this study, an evaluation was conducted on the present state of various ISS designs in order to make advanced adjustments and research to increase the productivity of the ISS in order to meet the rising need for potable water. According to this analysis, active ISS and hybrid ISS are shown to be the most successful ISS methods.